The Influence of Type and Serum Concentration to Oocyte Maturation Level on Sheep In Vitro - Wattimena, J; Tagama, TR; Hadisutanto, B (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
The objective of the research was to know the effect of serum type and concentration on in vitro maturation ovine oocyte. The result was expected to give information about the effect of serum type and concentration on in vitro maturation ovine oocyte, in order to find an alternative serum to reduce the use of serum from pharmacy industry. The result of research shows that concentration and type of serum significantly (P<0,05) influenced the maturation rate germinal vesicle (GV), germinal vesicle breakdown (GVBD), metaphase-I (M-I) and metaphase-II (M-II) phase. The result of research shows that concentration and tyoe of serum has no significant (P>0,05) influence on cumulus expansion rate grade 0, 1 and 2. (Animal Production 8(2): 94-99 (2006)Â Key Words: Oocyte, Maturation, Sheep